Stability of Non-Linear Constitutive Formulations for Viscoelastic Fluids - Siginer, Dennis A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Stability of Non-linear Constitutive Formulations for Viscoelastic Fluids provides a complete and up-to-date view of the field of constitutive equations for flowing viscoelastic fluids, in particular on their non-linear behavior, the stability of these constitutive equations that is their predictive power, and the impact of these constitutive equations on the dynamics of viscoelastic fluid flow in tubes. This book gives an overall view of the theories and attendant methodologies developed independently of thermodynamic considerations as well as those set within a thermodynamic framework to derive non-linear rheological constitutive equations for viscoelastic fluids. Developments in formulating Maxwell-like constitutive differential equations as well as single integral constitutive formulations are discussed in the light of Hadamard and dissipative type of instabilities.
Introduction -- Constitutive Formulations -- Epilogue -- Appendix I: Fréchet Derivative Expansion of the Integral Fluid of Order Three.
Keywords: Engineering; Materials; Hydraulic engineering; Surfaces (Physics).; Engineering; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer; Continuum Mechanics and Mechanics of Materials; Surfaces and Interfaces, Thin Films